Dictionary of the British English Spelling System - Brooks, Greg (Open Book Publishers, 2015)
"This book will tell all you need to know about British English spelling. It’s a reference work intended for anyone interested in the English language, especially those who teach it, whatever the age or mother tongue of their students. It will be particularly useful to those wishing to produce well-designed materials for teaching initial literacy via phonics, for teaching English as a foreign or second language, and for teacher training. English spelling is notoriously complicated and difficult to learn; it is correctly described as much less regular and predictable than any other alphabetic orthography. However, there is more regularity in the English spelling system than is generally appreciated. This book provides, for the first time, a thorough account of the whole complex system. It does so by describing how phonemes relate to graphemes and vice versa. It enables searches for particular words, so that one can easily find, not the meanings or pronunciations of words, but the other words with which those with unusual phoneme-grapheme/grapheme-phoneme correspondences keep company. Other unique features of this book include teacher-friendly lists of correspondences and various regularities not described by previous authorities, for example the strong tendency for the letter-name vowel phonemes (the names of the letters <a, e, i, o, u>) to be spelt with those single letters in non-final syllables."